Implementation of Bumdes Financial Report Preparation in Accordance with Minister of Village Regulation No. 136 of 2022 - sunaryono (CV. AFDIFAL MAJU BERKAH, 2024)
This study is a compilation of how the preparation of financial statements is carried out in the Village-Owned Enterprises (Bumdes) in adherence to the Village Minister Regulation No. 136 of 2022. Both, quantitative and qualitative research which consist of interviews and documentary analysis, were carried out to ascertain the degree of compliance, difficulty and impact of the regulations in the regulatory implementation. The research reveals that most of the Bumdes' compliance is what has to be dealt with by the fact of limited resources and the Bumdes regulatory issues. Besides, the introduction of financial reporting brings about other advantages like transparency, accountability, and development opportunities for Bumdes. The study gives the guidance for the intensive training to be given and the collaboration of all the parties which would lead to the successful implementation of the project. In general, this study provides a review of the role of support from all parties in the sustainability of Bumdes and Bumdes efforts in the process to realize a developed and successful village.